wB1, a new white mutant of Aspergillus nidulans on linkage group VII - J. A. ROPER; M. WALKER (Fungal Genetics Reports, 1990)
Several patches of white conidia were seen in green colonies of the duplication strain proA1 pabaA6 adE20 biA1;Dp(IR IIR)yA2, grown on 10(-2) M isonicotinic acid hydrazide; one with a mutation now designated wB1, has been analyzed.